Media Effects on Bystander Intervention: The Role of Exemplification, Framing, Risk Perception, and Motivations - Krämer, Benjamin (Journal of interpersonal violence, 2021)
This study examines how media coverage of bystander intervention affects helping behavior in similar situations, taking into account the role of motivations for and against helping. In a 2 × 4 factorial online experiment, a newspaper report on a case of bystander intervention was varied in terms of a (a) good versus bad outcome for the helper and (b) four types of framing targeting motivations for and against helping. Results show that risk perception, rejection of responsibility, motivation by social approval, and moral motivation are highly associated with the intention to intervene and with projected behavior. However, hardly any media effects on these factors could be found. Nevertheless, our findings hint at other paths of media influence on helping behavior.